The resilience of the food supply chain to pandemic COVID-19 - Khandaker, Hafiza (2021)
Today’s business climate is subject to a variety of challenges associated with environmental turbulence that demands resilience to achieve sustainable business. The rare external disruption by a natural cause like a pandemic directly affects the organization’s ability to continue its operations from getting raw materials from suppliers to provide finished goods to market. The aim of this thesis is to understand the present resilience system in the food supply chain in the grain industry in response to a pandemic through a qualitative case study methodology. It focuses more on the risks which are external to the focal firm where the cooperative Lantmännen’s grain supply chain is the case. The results from empirical data that came from the semi-structured and in-depth interviews suggest that appropriate application and practices of the resilience ideas can make a supply chain robust and withstand any kind of environmental turbulence to attain business continuity. This thesis finds that how has the resilience practices by the leading grain industry of Sweden increased its capability of operating even in an unprecedented event like the Corona pandemic. Lantmännen’s existing structure, supply chain design and the combination of global and local supply chain strategies gave them an edge to manage their operation and supply chain in a good way. Moreover, its diversified business portfolio, existing risk management culture and intense collaboration with upstream and downstream supply chain actors supported their business continuation despite the disturbance created by the pandemic. This existing proactive resilience mechanism has backed their managers to be agile to take the reactive measures very quickly to adjust to the new situation of the pandemic. According to the literature, the supply chain resilience increases the ability of an organization to endure, adjust and grow even in the turbulent situation, findings on Lantmännen’s supply chain confirms the justification and validation of the effect of resilience practices.